Sunshine in Korea : the South Korean debate over policies toward North Korea - Levin, Norman D.; Han, Yong-sŏp, 1955- (RAND, 2002)
The debate in South Korea over the government's engagement policy toward North Korea (the so-called "sunshine" policy) did not start with Pyongyang's recent admission that it has been secretly pursuing a nuclear weapons program in violation of multiple international commitments. However, the evolution of the debate will be an important determinant of how the South Korean and broader international response to this latest North Korean challenge ultimately ends. Examining the public South Korean debate over dealings with North Korea, this book reviews the relevant historical background, focusing on the evolution of "engagement" as the goal of South Korean policy toward the North. It examines the critical assumptions and central concepts motivating the new policy adopted by President Kim after his inauguration and analyzes the key issues in the public debate over this new policy. It also identifies the major actors and describes their respective positions on the government's approach to North Korea, as well as how these actors have affected public debate over government policy. The book concludes by assessing the sources of public controversy existing today, the likely short-term effects on South Korean policy, and the potential longer-term implications for South Korea, the United States, and U.S.-South Korean relations